Micro powder injection molding of micro-features - Chew, Reagan Wei Hon (2014)
Micro powder injection molding (PIM) is used in manufacturing process to create complex shaped parts at economical cost. PIM process consist of four main steps which are mixing, injection molding, debinding and sintering. To obtain a good outcome of the final product, each process needs to be executed properly. A circular part with micro-structures was molded in this project. There were a total of eleven micro-structures in each molded part. One feedstock were used which consisted of 92 weight % 316L stainless steel powder and 8 weight % binder system. The binder components consisted of paraffin wax (PW), ethylene vinyl acetate (EVA460), low density polyethylene (LDPE) and stearic acid (SA). The main focus of this project was to study the effects of injection molding parameters on the molded parts. The effects of different sets of molding conditions on the molded parts were compared qualitatively and quantitatively. Qualitative measures like micrographs images of the molded parts using Scanning Electron Microscope were used for observations. In the beginning of the experiments, the barrel temperature was taken as a variable to find the optimum barrel temperature for complete filling of micro-structures. Barrel temperature at 175 ⁰C was the best barrel temperature as the SEM micrographs shown very positive results. Although the micro-structures were completely filled using barrel temperature of 175 ⁰C, it appeared there are voids on the surfaces of the micro-structures and micro-channels when viewed under SEM. Molding temperature was then set as variable to minimize the effects of surface voids. Having a mold temperature of 80 ⁰C was the best among the rest as it appears to have the least of surface voids. As for quantitative measures, confocal imaging was done to measure the dimensions on the micro-structures of the molded part. Upon observations, good parts were singled out and sent for debinding. The debound parts were viewed under the SEM for debinding defects and shape retention of the micro structures. After debinding, the parts were sent for the final step which is sintering. The sintered part also went through visual and dimensional check using SEM and confocal imaging.